2021
DOI: 10.1186/s12944-021-01528-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alirocumab on coronary plaque in patients with coronary artery disease assessed by optical coherence tomography

Abstract: Background Proprotein convertase subtilisin kexin type 9 (PCSK9) inhibitors have been demonstrated to produce significantly greater reduction in LDL cholesterol levels and cardiovascular events than standard statin therapy. However, evidence on the impact of PCSK9 inhibitors on coronary plaque composition and morphology is limited. Methods In this open-label randomized study, eligible patients with intermediate coronary lesions and elevated LDL cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…To the best of our knowledge, this was the first study to investigate the effects of PCSK9 inhibitors on CAC progression in a randomized controlled study comparing PCSK9 inhibitors vs. standard statins therapy in patients with coronary artery disease. Previous intravascular ultrasound studies demonstrated that the use of PCSK9 inhibitors resulted in a greater reduction in total atheroma volume compared to statin monotherapy (12,13), and the primary results of our study with optical coherence tomography analysis showed that the addition of PCSK9 inhibitors to statins were associated with greater increases in fibrous cap thickness and reduced lipid arc (15,22). The GLAGOV trial showed that the use of evolocumab vs. statins did not produce differential changes in the percentage of plaque occupied by dense calcium assessed by virtual histology ultrasound (12).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…To the best of our knowledge, this was the first study to investigate the effects of PCSK9 inhibitors on CAC progression in a randomized controlled study comparing PCSK9 inhibitors vs. standard statins therapy in patients with coronary artery disease. Previous intravascular ultrasound studies demonstrated that the use of PCSK9 inhibitors resulted in a greater reduction in total atheroma volume compared to statin monotherapy (12,13), and the primary results of our study with optical coherence tomography analysis showed that the addition of PCSK9 inhibitors to statins were associated with greater increases in fibrous cap thickness and reduced lipid arc (15,22). The GLAGOV trial showed that the use of evolocumab vs. statins did not produce differential changes in the percentage of plaque occupied by dense calcium assessed by virtual histology ultrasound (12).…”
Section: Discussionsupporting
confidence: 56%
“…Subgroup analyses on the effects of statin dose adjustments and combined lipid lowering therapy cannot be performed as well. Second, the current study was a secondary analysis of a randomized study (15), in which CTA was not mandatary to all patients at baseline, and therefore it might introduce some potential bias into the study. Third, the relatively small number of patients in each group also limited the power of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 47 ] and the Alirocumab for Thin-Cap Fibroatheroma in Patients with Coronary Artery Disease Estimated by Optical Coherence Tomography (ALTAIR) trial [ 48 ] reported that the addition of alirocumab to statins also has a role in promoting a more stable plaque phenotype, in addition to the LDL-C–lowering effects. Treatment with alirocumab 75 mg twice monthly in addition to atorvastatin or rosuvastatin was associated with greater reductions in LDL-C, greater increases in fibrous cap thickness, and greater decreases in maximum lipid arc compared with standard statin monotherapy [ 47 ]. On the other hand, in the ODYSSEY J-IVUS trial by Ako et al.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effects of statin combined with PCSK9i might be attributed to the stabilization and regression of residual vulnerable coronary plaques in patients with CAD [ 17 ]. Based on the current recommended guidelines, PCSK9i administration is likely to be considered for patients with a very high CAD risk, so its administration may contribute to secondary prevention in patients with non-culprit segment plaques regardless of plaque vulnerability [ 18 , 19 ]. Even after combining statins, ezetimibe and PCSK9i, some patient subgroups fail to achieve LDL-C targets requiring alternative treatments.…”
mentioning
confidence: 99%